The criminal careers of those imprisoned for hate crime in the UK - Jolliffe, Darrick (European journal of criminology, 2020)
Hate crime research has increased, but there are very few studies examining hate crime offenders. It is, therefore, difficult to determine to what extent those who perpetrate this offence might be different from those who have not committed hate crime. This study is the first to provide an account of the demographics and criminal histories of those serving time in prison for committing a hate crime. It is based on a large complete population of offenders in the UK. Hate crime offenders released from prison were found to have prolific criminal careers, having committed a wide range and large number of different types of offences. When compared with those who committed a general (non-hate) violent offence, violent hate crime offenders were significantly older and were considerably more prolific in their previous offending. Violent hate crime appeared quantitatively, as opposed to qualitatively, different from violent non-hate crime, but this was less clearly true when those who had committed public order hate crime were compared with other public order offenders. Interventions to reduce the later offending of violent hate crime offenders should be based on the effective interventions that exist for violent offenders, but should take into account knowledge about the surprisingly prolific criminal careers of hate crime offenders.